Chronic disease and recent addiction treatment utilization among alcohol and drug dependent adults - Samet Jeffrey; Allensworth-Davies Donald; Cheng Debbie M; Larson Mary Jo; Reif Sharon; Saitz Richard (BMC, 2011)
Abstract Background Chronic medical diseases require regular and longitudinal care and self-management for effective treatment. When chronic diseases include substance use disorders, care and treatment of both the medical and addiction disorders may affect access to care and the ability to focus on both conditions. The objective of this paper is to evaluate the association between the presence of chronic medical disease and recent addiction treatment utilization among adults with substance dependence. Methods Cross-sectional secondary data analysis of self-reported baseline data from alcohol and/or drug-dependent adults enrolled in a randomized clinical trial of a disease management program for substance dependence in primary care. The main independent variable was chronic medical disease status, categorized using the Katz Comorbidity Score as none, single condition of lower severity, or higher severity (multiple conditions or single higher severity condition), based on comorbidity scores determined from self-report. Asthma was also examined in secondary analyses. The primary outcome was any self-reported addiction treatment utilization (excluding detoxification) in the 3 months prior to study entry, including receipt of any addiction-focused counseling or addiction medication from any healthcare provider. Logistic regression models were adjusted for sociodemographics, type of substance dependence, recruitment site, current smoking, and recent anxiety severity. Results Of 563 subjects, 184 (33%) reported any chronic disease (20% low severity; 13% higher severity) and 111 (20%) reported asthma; 157 (28%) reported any addiction treatment utilization in the past 3 months. In multivariate regression analyses, no significant effect was detected for chronic disease on addiction treatment utilization (adjusted odds ratio [AOR] 0.88 lower severity vs. none, 95% confidence interval (CI): 0.60, 1.28; AOR 1.29 higher severity vs. none, 95% CI: 0.89, 1.88) nor for asthma. Conclusions In this cohort of alcohol and drug dependent persons, there was no significant effect of chronic medical disease on recent addiction treatment utilization. Chronic disease may not hinder or facilitate connection to addiction treatment.